The Sabbath and the sanctuary: access to God in the Letter to the Hebrews and its priestly context - Calaway, Jared C. (Wissenschaftliche Untersuchungen zum Neuen Testament, 2013)
Hauptbeschreibung: Who can enter the sacred and heavenly presence of God? And how? Various ancient Jewish and emergent Christian groups disputed these questions in the first century CE. Jared C. Calaway states that the Letter to the Hebrews joined this debate by engaging and countering priestly frameworks of sacred access that aligned the Sabbath with the sanctuary. From the Hebrew Bible through late Second Temple Judaism, the sanctity of the sanctuary could be experienced through the Sabbath, sacred space through sacred time. In its sweeping vistas of Sabbath rest and the heavenly homeland, th